Disain Sistem Basis Data Usaha Kecil dan Menengah (UKM) Agroindustri (Studi Kasus Pada UKM Tempe) - Mulyarto, Aunur R.; Purwaningsih, Isti (Fakultas Teknologi Pertanian Universitas Brawijaya, 2004)
The objective of this research is to set up data base system of SME, particularly for tempe agroindustry with emphasizing on conceptual and logical design. Primary data was collected via deep interview and secondary data from any documents that related to the study research design includes identification and need analysis, conseptual design (build the Entity-Relationship model) and logical design (build the Relational Data Model) Base on the identification and need analysis, there were seven associated actors i.e. SME, cooperation, finance institutions, raw-material supplier, product supplier, local government and consument. Conceptual model was built using Entity-Relationship Diagram. There was seven entity sets and seven relation sets with one-to-many cardinality for the whole relationships. Transformation from Entity-Relationship Model to Relational Data Model produced 14 tables, include: Perajin, Koperasi, Penyalur, LembKeu, Modal, Produk, BahanBaku, Menjual, Menyalurkan, Menggunakan, Meminjam, Menyediakan, Menghasilkan, and MenjadiAnggota. Each table had attributes completed with data type and data domain. Key words : Database, Agroindustry, Conceptual Model, Small and Medium Enterprise